The Geographical Elements Adaptation in Touristic Projects: Study Area (Heet District, Anbar-Iraq) - Alrawi, Abdulnaser Sabri Shaher (International Journal of Psychosocial Rehabilitation, 2020)
Tourism is one of the important economic activities that contribute to increasing the national income of many countries of the world. It attracts a significant proportion of the workforce. Despite the availability of various capabilities required by the tourism activity, including deserts, topography, coasts, forests, climate diversity and cultural heritage, the tourism activity is still an activity. Limited in various regions of Iraq. From this standpoint, this topic was chosen to shed light on the natural and human components present in the place and how to invest them in order to be tourist centers at the local and international level. The Heet district of Anbar Province in Iraq was chosen as a study area because it is located within a desert area with a wonderful natural environment where it passes through Euphrates River. It represents one of the ancient places of human stability. It contains many archaeological sites, the most important of which is the Heet castle. The researcher identified the problem of research in asking about the natural and human potentials that the Heet district enjoys and can be invested in establishing tourism projects. In order to answer what was mentioned in the scientific question, the research hypothesis was determined that the study area possesses a set of natural and human potentials that represent important pillars for undertaking various tourism activities to be a tourist attraction center at the local and international level. The most important natural and human components and archaeological sites that constitute the raw material that can be invested in the tourism industry in the study area were reviewed. In light of the available data, the researcher presented a strategy for sustainable tourism development.